Hubungan Pengetahuan Remaja, Pergaulan, dan Pengawasan Orang Tua terhadap Resiko Pernikahan Dini - salaka, lisda novita; Hanifa, Fanni; Noviyani, Ernita Prima (Journal of Nursing Education and Practice, 2024)
Introduction: Adolescence is a period of transition from the childhood phase to the maturity phase. During this period there are changes both mentally, physically, and emotionally and it becomes a very important phase for someone because of that, this phase becomes a phase for them to find their identity. One of the things that should be a concern in this case is early marriage because it occurs in the teens. The role of parents in the family is very important to reduce the number of underage child marriages, in North Maluku province, cases of underage child marriage cross national boundaries. Objectives: The aim was to get an overview of the relationship between adolescent social knowledge and parental supervision of the incidence of early marriage in Kukumutuk Village in 2022. Subjects in This study were adolescents aged 15-19 years in Kukumutuk Village. Method: The type of research used in this study was descriptive quantitative with a cross-sectional design. The sample in this study consisted of 78 teenagers aged 15-19 years. The researcher used a total sampling technique in taking the sample. The data collection instrument uses a questionnaire. Data analysis in this study used univariate analysis and bivariate analysis with the chi-square test. Result: The relationship between the level of knowledge of adolescents and the incidence of early marriage was obtained by p-value = 0.000 < α = 0.05. The relationship between social relations and the incidence of early marriage was obtained by p-value = 0.000 < α=0.05. The relationship between parental supervision and the incidence of early marriage was obtained by p-value = 0.00 < α = 0.05. Conclusion: There is a relationship between the level of adolescent knowledge, social interactions, and parental supervision and the incidence of early marriage in Kukumutuk Village, Kao Subdistrict in 2022.